RELEVANSI NILAI-NILAI PENDIDIKAN ISLAM TERHADAP CITA INDONESIA EMAS 2045 DALAM TINJAUAN AL-QUR’AN - Dikriyah; Suprihatin; Akhmad Kharis Kurniawan; Reffy Ananda Rizki (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2025)
This study aims to examine the relevance of Islamic educational values to the vision of Indonesia Emas 2045 from the perspective of the Qur’an. Indonesia Emas 2045 represents the national aspiration to realize a developed, competitive, just, and morally upright nation. Islamic education, as a system grounded in divine values, plays a fundamental role in shaping human resources that are intellectually, spiritually, and morally excellent. This research employs a qualitative approach using the thematic exegesis (tafsīr maudhu‘ī) method, analyzing Qur’anic verses related to education, human potential development, and character formation. The findings indicate that Qur’anic values such as integrity, responsibility, wisdom, competence, intelligence, and moral virtue constitute the core foundation for the holistic development of the Indonesian people. These values provide the ethical and spiritual basis for Islamic education in preparing a generation that is characterized, productive, and globally competitive. Thus, Islamic education from the Qur’anic perspective has a strong relevance in supporting the realization of the Indonesia Emas 2045 vision—an advanced, civilized nation oriented toward the common good.